2002
DOI: 10.3390/i3040310
|View full text |Cite
|
Sign up to set email alerts
|

Use of Local Softness for the Interpretation of Reaction Mechanisms

Abstract: Abstract:The application of reactivity parameters derived from density functional theory in a local sense, in particular the softness and Fukui function, to interpret and predict the mechanisms of various organic reactions has been discussed. Local softness is shown to be successful in determining the site-selectivity and regiochemistry and can be used as an alternative to the traditional frontier orbital theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…The Fukui function f ðrÞ [9][10][11] is defined as a derivative of electronic density qðrÞ versus number of electrons N at a constant external potential mðrÞ (fixed nuclei):…”
Section: Fukui Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fukui function f ðrÞ [9][10][11] is defined as a derivative of electronic density qðrÞ versus number of electrons N at a constant external potential mðrÞ (fixed nuclei):…”
Section: Fukui Functionmentioning
confidence: 99%
“…Our former calculations on models systems [7,8] have shown that the condensed Fukui function [9][10][11] can be useful in the prediction of the reactivity in silico of highly symmetrical and highly delocalized molecules like nanotubes and fullerenes. A novelty of the present study is the development of a simple model to predict the reactivity of conjugated polycyclic aromatic hydrocarbons of the general formula C 6n 2 H 6n with hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The final global reactivity descriptor, molecular softness, is inversely related to the molecular hardness. 19,20,22 Local QC indices describe properties of atoms in a molecule. The atomic charge provides a local reactivity index that is defined as the difference between the nuclear charge and the total (inner and valence) electron density attributed to the atom.…”
Section: Introductionmentioning
confidence: 99%
“…15,21,22 Softness is the Fukui function scaled by the molecular hardness. 19 Consequently reactivity values may be compared between atoms in different molecules using the atomcondensed softness.…”
Section: Introductionmentioning
confidence: 99%
“…Fukui function f r ð Þ [19][20][21] is defined as a derivative of electronic density q r ð Þ versus the total number of electrons N at constant external potential v generated by the nuclei. Thus,…”
Section: Theoretical Backgroundmentioning
confidence: 99%